2021
DOI: 10.1016/j.ebiom.2021.103678
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Mediated Exonic Disruption for HIV-1 Elimination

Abstract: Background A barrier to HIV-1 cure rests in the persistence of proviral DNA in infected CD4+ leukocytes. The high HIV-1 mutation rate leads to viral diversity, immune evasion, and consequent antiretroviral drug resistance. While CRISPR-spCas9 can eliminate latent proviral DNA, its efficacy is limited by HIV strain diversity and precision target cell delivery. Methods A library of guide RNAs (gRNAs) designed to disrupt five HIV-1 exons ( tat … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Studies have demonstrated that using lentiviral-based CRISPR-Cas9 and several gRNA targets for different regions of HIV-1 provirus DNA has reduced HIV-1 replication by more than 96% [ 59 ]. Thus, the use of viral vectors to express Cas9 and multiple gRNA targets can be more successful in targeting HIV-1 provirus DNA [ 63 , 64 , 65 ]. Some studies have suggested the concomitant use of CRISPR/Cas9 and antiretroviral drugs or RNA interference (RNAi) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that using lentiviral-based CRISPR-Cas9 and several gRNA targets for different regions of HIV-1 provirus DNA has reduced HIV-1 replication by more than 96% [ 59 ]. Thus, the use of viral vectors to express Cas9 and multiple gRNA targets can be more successful in targeting HIV-1 provirus DNA [ 63 , 64 , 65 ]. Some studies have suggested the concomitant use of CRISPR/Cas9 and antiretroviral drugs or RNA interference (RNAi) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of viral vectors to express Cas9 and multiple gRNA targets can be more successful in targeting HIV-1 provirus DNA [63][64][65]. Some studies have suggested the concomitant use of CRISPR/Cas9 and antiretroviral drugs or RNA interference (RNAi) [66].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Each method has advantages and disadvantages, and depending on the intended application and target cell type, the right delivery method should be selected. These methods can be based on viral delivery [ 51 , 52 , 53 , 54 ] or lipid vector delivery of the CRISPR/Cas9 system [ 55 ], but genome editing can also be facilitated through fusion of the Cas9 protein to cell-penetrating peptides [ 56 ], or by directly electroporating the CRISPR/Cas9 system into cells of interest [ 27 , 55 , 57 , 58 ]. Interestingly, recently, the mechanism HIV-1 employs to target CD4 + T cells has been repurposed as a tool to direct viral particles containing the Cas9 system specifically to cells expressing CD4, i.e., T cells [ 59 ], opening up new potential avenues with this addition to the CRISPR/Cas9 toolbox [ 60 ], e.g., in vivo gene editing of CD4 + T cells.…”
Section: Gene Editing Basics—mode Of Action and Different Toolsmentioning
confidence: 99%
“…CRISPR could also be used to directly target the HIV-1 genome and remove it from infected cells, for instance by targeting the HIV viral promoter long terminal repeat [ 55 ]. Importantly, in vitro experiments showed up to 100% viral excision [ 55 ]. While currently not employed as a therapeutic strategy yet, the approach is interesting.…”
Section: Targeting the Hiv Viral Reservoirmentioning
confidence: 99%
“…In the future, CRISPR/SaCas9 and Ribonucleoprotein (RNP) administration should be explored in the further investigations. 108 As well as some different title studies were explained the effectiveness of the CRISPR gene editing technology on the management of HIV/AIDS including: CRISPR view of hematopoietic stem cells: Moving innovative bioengineering into the clinic, 104 CRISPR-Edited Stem Cells in a Patient with HIV and Acute Lymphocytic Leukaemia, 109 Sequential LASER ART and CRISPR Treatments Eliminate HIV-1 in a Subset of Infected Humanized Mice, 110 Extinction of all infectious HIV in cell culture by the CRISPR-Cas12a system with only a single crRNA, 111 HIV-specific humoral immune responses by CRISPR/Cas9-edited B cells, 112 CRISPR-Cas9 Mediated Exonic Disruption for HIV-1 Elimination, 113 RNA-directed gene editing specifically eradicates latent and prevents new HIV-1 infection, 114 CRISPR/Cas9 Ablation of Integrated HIV-1 Accumulates Pro viral DNA Circles with Reformed Long Terminal Repeats, 115 CRISPR-Cas9-mediated gene disruption of HIV-1 co-receptors confers broad resistance to infection in human T cells and humanized mice, 116 Inhibition of HIV-1 infection of primary CD4+ T-cells by gene editing of CCR5 using adenovirus-delivered CRISPR/Cas9, 117 Transient CRISPR-Cas Treatment Can Prevent Reactivation of HIV-1 Replication in a Latently Infected T-Cell Line, 118 CCR5 Gene Disruption via Lentiviral Vectors Expressing Cas9 and Single Guided RNA Renders Cells Resistant to HIV-1 Infection, 119 CRISPR/Cas9-Mediated CCR5 Ablation in Human Hematopoietic Stem/Progenitor Cells Confers HIV-1 Resistance In Vivo. 109 …”
Section: Crispr and Stem Cell Applicationsmentioning
confidence: 99%